Bubble continuous positive airway pressure as a primary modality of respiratory support in meconium aspiration syndrome - Ahmed, F K Riyaz; Jeergal, Nazeer Ahmad; Channakeshava, Devika; Reddy, Laxmi Narayana (Indian Journal of Child Health, 2019)
Background: Approximately 3–4% of neonates with meconium-stained amniotic fluid (MSAF) develop meconium aspiration syndrome (MAS), of which nearly 30–50% need continuous positive airway pressure (CPAP) or mechanical ventilation (MV). Objective: The objective of the study was to evaluate the usefulness of bubble CPAP as a respiratory support in neonates admitted with MAS and to enumerate factors affecting the CPAP failure. Materials and Methods: A prospective study was conducted, involving all the neonates born with a history of MSAF with respiratory distress within 6 h of life (Downe’s score 4–7), SpO2 90% with FiO2 requirement